PHOTODYNAMIC THERAPY IN THE TREATMENT OF PERIODONTAL DISEASE - Maria-Alexandra Martu; Irina-Georgeta Sufaru; Ionut Luchian; Anamaria Zaharescu; Liviu Manole; George-Alexandru Maftei; Daniel Acatrinei; Silvia Martu (Romanian Dental Association for Education, 2019)
Biofilms that colonize tooth surfaces and epithelial cells lining the periodontal pocket ⁄ gingival sulcus (subgingival dental plaques) are among the most complex biofilms that exist in nature. Photodynamic therapy has been suggested as an alternative to chemical antimicrobial agents to eliminate subgingival species and treat periodontitis. Antimicrobial photodynamic therapy seems to be a unique and interesting therapeutic approach towards the treatment of periodontitis and peri-implantitis. The results of a number of in vitro studies clearly demonstrate the effective and efficient bactericidal effect of antimicrobial photodynamic therapy. Antimicrobial photodynamic therapy may hold promise as a substitute for currently available chemotherapy in the treatment of periodontal and peri-implant diseases.